Your Finger, your Tiger: Netiquette Violations of the Microcelebrity Parody Content on Social Media - Astuti, Yanti Dwi; Zamroni, Mohammad (MediaTor (Jurnal Komunikasi), 2022)
Netiquette is still lacking among Indonesian netizens. One of the netiquette violations was carried out by micro-celebrities Tri Suaka and Zinidin Zidan, who virally recorded and distributed mocking parody videos of Andika Kangen Band. This research aims to uncover the phenomenon of the practice of violating netiquette by microcelebrities using the constructivism paradigm with qualitative content analysis methods in order to draw a conclusion from the meaning of a text in the video. The audience here plays two roles at once, namely consumers and producers. The theories used are of Digital Literacy, Social Media and Netiquette. The results of the study reveal that internet ethics violations occur due to the anonymous and confidential nature of digital media resulting in no recognition of identity, misinterpretation of digital rights related to unlimited freedom of expression, and excessive use of social media time by netizens. Research has also found that netizens more easily show attitudes and opinions that are usually hidden from others due to social and economic conditions that make them anxious and frustrated, consumption of and belief in hoaxes, low awareness of ethics and morality, and lack of understanding about sanctions for ethical violations related to digital media.